Geochemical analysis of the truncated Viking Age trading settlement of Heimdalsjordet, Norway. Issue 5 (18th May 2020) - Cannell, Rebecca J. S.; Bill, Jan; Cheetham, Paul; Welham, Kate
Abstract: Single and multielement archaeological geochemistry has been applied to research and rescue projects for many decades to enhance our understanding of the past use of space. Often applied on one contextual plane, this ignores the complex palimpsest resulting from past occupation and soil processes. Furthermore, many important sites are now heavily truncated by plowing, leaving little more than negative features below the homogenized topsoil. These challenges require new approaches to archaeological geochemistry to gather information before these sites are lost to modern land use. The research presented here applied coring as a sampling method on a truncated site, the sample locations guided by high‐resolution ground‐penetrating radar data and excavation, before using portable X‐ray fluorescence directly on the core samples to understand the phase by phase composition of the deposits and thus past human occupation. The results suggest that even in truncated and secondary contexts, such as the case study of the Viking Age trade settlement of Heimdalsjordet, Norway, archaeological geochemistry can give insight into the chronological and spatial development of the site, and is especially relevant for detecting nonferrous metalworking activity.